The creativity of God world, Eucharist, reason - Davies, Oliver 1956- (Cambridge studies in Christian doctrine, 2004)
We have, as a theological community, generally lost a language in which to speak of the created-ness of the world. As a consequence, our discourses of reason cannot bridge the way we know God and the way we know the world. Therefore, argues Oliver Davies, a primary task of contemporary theology is the regeneration of a Christian account of the world as sacramental, leading to the formation of a Christian conception of reason and a new Christocentric understanding of the real. Both the Johannine tradition of creation through the Word and a Eucharistic semiotics of Christ as the embodied, sacrificial and creative speech of God serve the project of a repairal of Christian cosmology. The world itself is viewed as a creative text authored by God, of which we as interpreters are an integral part. This is a wide-ranging and convincing book that makes an important contribution to modern theology